Analysis and Design of Digital Marketing Information System for Building Material Store - Elfin Saputra; Bernardus Alvin Rig; Octa Hutapea; Radyan Rahmananta; Agung Mulyadi Purba; Yerik Afrianto Singgalen (Universitas Bina Darma, 2023)
The manual nature of Material Store such as Toko Bangunan Berkat Rezeki's current business operations is one of the hurdles it encounters in marketing. This study intends to build a marketing information system for the products and services of Toko Bangunan Berkat Rezeki utilizing the 4P marketing mix idea (product, price, place, and promotion). The framework for application design is design thinking, which includes empathy, defining, ideating, prototyping, and test phases. Business owners, employees, and customer's requirements are identified during the empathize phase. In addition, at the designated stage, each system user's business operational difficulties are ranked according to a scale of importance. At the ideate stage, the outcomes of selecting and organizing problems and wants of system users based on priority scales are used to create flows and authorities according to their respective functions. At the prototype stage, the application interface is designed based on the demands and rules of system users and follows the 4P marketing mix concept. In the testing phase, test the login procedure for each user and the procedures for adding, saving, viewing, updating, and removing data. The findings of this study indicate that information on products, product prices, and product promotions may be handled by a website-based marketing information system, such that place is no longer synonymous with a physical store but rather an intangible one. Consequently, Toko Bangunan Berkat Rezeki can employ a website-based marketing information system to enhance sales volume and expand its market reach.